Two equations for estimating the exergy of woody biomass based on the exergy of ash. (1st July 2016) - Zhang, Yaning; Zhao, Wenke; Li, Bingxi; Zhang, Haochun; Jiang, Baocheng; Ke, Cunfeng
Abstract: Szargut et al. [1] proposed an appropriative equation for calculating the exergy of woody biomass. Cumbersome work is involved in calculating the exergy of woody biomass as the complicated ash compositions are included for obtaining the ash exergy in the equation. Based on the exergy values of ash contents of sixty four woody biomass investigated in this study, the average value of wood ash is obtained and a positive linear relationship between ash exergy and ash content is observed. An equation based on the average exergy of wood ash with relative errors of −0.76% to 1.38% and another equation based on the relationship between ash exergy and ash content with relative errors of −1.16% to 0.88% are observed. These two easier equations can be well used for expeditious estimation of the exergy of woody biomass with high accuracies. Highlights: The exergy values of sixty four wood ashes are investigated. An equation based on the average exergy of wood ash is proposed. An equation based on the relationship between ash exergy and ash content is proposed.